(Table T1) Major ion concentrations of interstitial waters from six ODP Leg 201 sites - Catherine M Donohue; Glen T Snyder; Gerald Roy Dickens (PANGAEA, 2006)
Leg 201 of the Ocean Drilling Program (ODP) focused on understanding subsurface microbial communities and their influence on the chemistry of the surrounding environment (D extquotesingleHondt, Jørgensen, Miller, et al., 2003, doi:10.2973/odp.proc.ir.201.2003). During the cruise, sediment cores were collected from four different marine environments of the eastern Pacific Ocean: deep open ocean beneath the moderately productive upwelling regime of the equator (Sites 1225 and 1226), shallow waters of the highly productive Peru shelf (Sites 1227-1229), a deepwater gas-charged zone in the Peru Trench (Site 1230), and a deep open-ocean area under oligotrophic waters (Site 1231). Each of these sites had been drilled previously (during either Deep Sea Drilling Project [DSDP] Leg 34, ODP Leg 112, or ODP Leg 138), although not for detailed microbiological or geochemical investigations. Interstitial waters are routinely analyzed for major cations aboard the JOIDES Resolution drillship. An exception was made during Leg 201 because other dissolved species (e.g. Fe2+, Mn2+, Ba2+, and acetate) were of more immediate interest and because low-resolution profiles of major cations already existed from the earlier cruises (D extquotesingleHondt, Jørgensen, Miller, et al., 2003, doi:10.2973/odp.proc.ir.201.2003). Consequently, major cation analyses were withheld for shore-based work. We present here the Ca2+, Mg2+, K+, Na+, and Sr2+ concentrations for pore waters from six of the sites, Sites 1225-1230. Pore waters from Site 1231 are not included in this report because of data inconsistencies.
Supplement to: Donohue, CM et al. (2006): Data report: Major cation concentrations of interstitial waters collected from deep sediments of eastern equatorial Pacific and Peru margin (ODP Leg 201). In: Jørgensen, BB; D extquotesingleHondt, SL; Miller, DJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 201, 1-19, https://doi.org/10.2973/odp.proc.sr.201.104.2006